Pregorexia: Eating Disorder in Pregnancy - Meltem Puşuroğlu; Cicek Hocaoglu (Psikiyatride Güncel Yaklaşımlar, 2023)
Pregorexia, the eating disorder observed during pregnancy, is a condition that negatively affects the health of the mother and the baby. The frequency of thin body perception, which has entered our lives with popular culture, is increasing. Pregorexia negatively affects both the health of the mother and the development of the baby. Pregnancy is a complex physiological and spiritual period for the mother. First of all, clinicians should be careful about eating disorders during pregnancy. Pregnant women may be unnoticed in terms of eating disorders in the outpatient clinic. In the treatment duration, it is very important to inform the mother about the importance of nutrition during pregnancy. The mother should be informed about nutrition and psychiatric treatment support should be provided. It is important for clinicians to know about pregorexia, which is an important health problem for both mother and baby.